Pengaruh Metode Karyawisata Berkearifan Lokal Madura Terhadap Kemampuan Berpikir Kritis Siswa UPTD SDN 2 Tambaan di Daerah Wisata Pantai Camplong - Dya Qurotul A’yun; Ika Dian Rahmawati; Evy Maya Stefany (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: This study is aimed at knowing the implementation of field study for critical thinking skills and how far students can think critically on Science. This study is a quantitative descriptive using one group pretest-posttest experimental design. The subjects were 26 students of Tambaan Camplong Sampang Elementary School. To analyze the data, there are two techniques conducted. The first data analyzed is the qualitative descriptive on independent variable (field study method) which were collected through observation and interview. The second data analyzed is the dependent variable (critical thinking skills) which is analyzed using inferential parametric statistic, namely t-test one sample test. The data were collected from an essay test. The results of independent variable analysis show that 95 percent of the students agreed with the implementation of field study method. They also comprehended the materials which was indicated by asking questions, re-explained the materials, answered the worksheets which source was from questions about field study implementation, and drew a conclusion based on their own observation towards a particular object during the field study. They also found the materials explained by their teacher directly during the field study and thought that it was more interesting, funnier, and more meaningful. Moreover, the results of dependent variable analysis show that the mean of pretest is 56.67 with St.deviation 7.188, and the mean of posttest is 86.15 with St.deviation 5.940. In addition, the result of t-test shows that sig (2-tailed) 0.000 less than α (0.05), meaning that the students’ critical thinking skills is more than 70 percent of the expected criteria. Abstrak: Penelitian ini bertujuan untuk mengetahui pelaksanaan metode karyawisata terhadap kemampuan berpikir kritis dan seberapa tinggi kemampuan berpikir kritis siswa pada mata pelajaran IPA. Jenis penelitin ini deskriptif kuantitatif dengan desain eksperimen one grup pretest-postest. Sampel yang digunakan sebanyak 26 siswa SDN Tambaan Camplong Sampang. Teknik analisis data pertama deskriptif kualitatif pada variabel bebas yakni metode karyawisata dengan teknik pengumpulan data observasi dan wawancara, teknik analisis data kedua menggunakan statistik inferensial parametrik uji-t one simple test pada variabel terikat berpikir kritis dengan teknik pengumpulan data menggunakan tes tulis uraian. Hasil analisis variabel bebas metode karyawisata dapat disimpulkan bahwa 95 persen siswa setuju pada penerapan metode karyawisata, siswa memahami materi dengan cara berani bertanya, mampu menyampaikan kembali informasi dari materi yang telah diterima, dapat menjawab LKS yang bersumber dari pertanyaan- pertanyaan sekitar pelaksanaan karyawisata, menarik kesimpulan berdasarkan hasil pengamatan mereka sendiri terhadap objek ketika dilaksanakan karyawisata, menemukan secara langsung materi yang dijelaskan oleh guru sehingga pembelajaran menarik dan menyenangkan, dan lebih bermakna. Hasil analisis variabel terikat berpikir kritis mean pretes 56,67 dengan St deviation 7,118 dan mean postes 86,15 dengan St deviation 5,940 sedangkan uji-t Sig (2-tailed) 0,000 kurang dari α (0,05) artinya kemampuan berpikir kritis siswa lebih dari 70 persen dari kriteria yang diharapkan.